Implementation of Fuzzy Logic in Determining Dough Development Rate of Bakery Products - Andhea Sitoresmi Nurauliya; Fiqri Nurfadillah; Muhammad Danang Mukti Darmawan; Ester Angeline; Nanda Octavia; Syawaliyah Yahya; Rolan Natanael Sitinjak; Raida Dwiana Yasmin; Rafly Aulia Rahman; Putri Tampubolon; Nanda Rizki Utami; Nafla Hasna Alifa; Jeni Luthfi Araya; Ghina Sabillah; Arridho Fariz Alghifari; Amanda Atika Zahra; Mrr. Lukie Trianawati; Nafi'a Ikromatul Hasanah (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
Bakery is one of the dessert-making places that is popular with various circles. Good product quality is greatly influenced by the right roasting process. Temperature and proofing time are important factors for bakery products themselves. This research aims to analyze the effect of temperature and proofing time on bakery products using fuzzy implementation methods. The fuzzy method is a soft computing technique that mimics human decision-making processes to solve complex and uncertain problems. In this study, the fuzzy system was designed to control the oven temperature and the proofing time of bakery products. The fuzzy system has two inputs, namely temperature and proofing time, and one output, which is the bread development rate. The fuzzy rule is designed to determine the degree of bread proofing based on a combination of temperature values and proofing time. The results of the study with a case study of a baking temperature of 185°C and a proofing time of 115 minutes showed the level of bakery development with medium results. Calculations are done using manual method and Matlab application. The manual calculation yields a result of 6, which falls within the medium fuzzy rule, consistent with the data processing results in the MATLAB application.